2004
DOI: 10.1016/j.femsle.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Elaeagnus-compatible Frankia from soils collected in Tunisia

Abstract: The occurrence and diversity of Frankia nodulating Elaeagnus angustifolia in Tunisia were evaluated in 30 soils from different regions by a Frankia-capturing assay. Despite the absence of actinorhizal plants in 24 of the 30 soils, nodules were captured from all the samples. Eight pure strains were isolated from single colonies grown in agar medium. On the basis of 16S rRNA and GlnII sequences, seven strains were clustered with Frankia, colonizing Elaeagnaceae and Rhamnaceae in two different phylogenetic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 27 publications
1
42
1
Order By: Relevance
“…Slow growing, melanotrophic actinobacteria Actinobacteria Isolating Agar (AIA) Minimal medium Fast and slow growing actinobacteria (Baskaran et al, 2011) Defined Propionate Medium (DPM) and Buffered Ammonium Propionate (BAP) Specific for Frankia species (Gtari et al, 2004) International Streptomyces Project (ISP) Media (1 to 9)…”
Section: Medium Properties Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow growing, melanotrophic actinobacteria Actinobacteria Isolating Agar (AIA) Minimal medium Fast and slow growing actinobacteria (Baskaran et al, 2011) Defined Propionate Medium (DPM) and Buffered Ammonium Propionate (BAP) Specific for Frankia species (Gtari et al, 2004) International Streptomyces Project (ISP) Media (1 to 9)…”
Section: Medium Properties Referencesmentioning
confidence: 99%
“…The ISP (International Streptomyces Project) family media have been used for studying physiological characteristics of already isolated actinobacteria. Slow growing nitrogen fixing actinobacterial taxa belonging to genus Frankia that were found associated with actinhorizal plants, can be isolated in liquid media like buffered ammonium propionate (BAP) or defined propionate medium (DPM) (Gtari et al, 2004). Compared to Luedemann or AIA, these media are minimal and thus, limit colonization by fast growing bacteria.…”
Section: Actinobacteria Isolationmentioning
confidence: 99%
“…This is indicative of a larger diversity for Frankia nodulating Hippophae salicifolia compared to that nodulating alder. Elaeagnus compatible Frankia isolated from soils collected from Tunisia too showed large diversity [16]. On the other hand, Clawson et al [17] found a shallow level of diversity in the 16S rDNA analysis of family Elaeagnaceae.…”
Section: Nucleotide Sequencing and Analysismentioning
confidence: 99%
“…The 16S rRNA gene PCR products were purifi ed from PCR reaction mixtures using the QIAquick Wizard PCR Purifi cation Kit (Promega), according to manufacturers instructions. The sequences were determined by cycle sequencing using the Taq Dye Deoxy Terminator Cycle Sequencing Kit (Applied Biosystems, HTDS, Tunisia), and underwent fragment separation in an ABI Prism 3130 DNA sequencer as previously described (Gtari et al, 2004). Similarity matrix of 16S rRNA gene sequences with closest neighbors and identifi cation were achieved using the EzTaxon server (http://www.eztaxon.…”
mentioning
confidence: 99%
“…BOX-PCR was performed as described by Gtari et al (2004). Mixtures contained 1 PCR buf-fer, 2 mM MgCl 2 , 0.1 mM dNTPs, 0.8 µM of BOX-A1R primer, 5% of dimethylsulfoxide, 1.3 U of Taq DNA polymerase and standardized 15 ng of genomic DNA in a fi nal volume of 30 µl.…”
mentioning
confidence: 99%